Upgraded methyl oleate to diesel-like hydrocarbons through selective hydrodeoxygenation over Mo-based catalyst. (15th January 2022) - Yu, Cong; Yu, Shitao; Li, Lu
Graphical abstract: Highlights: An efficient and selective hydrodeoxygenation catalyst was synthesized. Synergistic catalysis of molybdenum oxide and molybdenum carbide. The selectivity was 96.8%, and the yield of unsaturated hydrocarbon was 41.9%. HHV of products (46.09 MJ/kg) was reached the standard of bio-diesel. Abstract: As an effective substitute for petroleum diesel oil, biodiesel has received much more attention. Moreover, the diesel-like hydrocarbons produced by hydrodeoxygenation can further reduce the oxygen content and have a higher calorific value. Herein, we synthesize MoO2 /Mo2 C catalyst and use it for the selective hydrodeoxygenation of methyl oleate to diesel-like hydrocarbons. In this study, the reaction is mainly proceeded through the hydrodeoxygenation route (HDO/DCO is 30.2), the ratio of C18 hydrocarbons in the products is 96.8%. The higher heating value (HHV) of the liquid products reached 46.09 MJ/kg. Meanwhile, the products contain 41.9% unsaturated hydrocarbons, which is attributed to the selective adsorption of carbon–oxygen bonds by oxygen vacancy in MoO2 . X-ray photoelectron spectroscopy (XPS) and electron spin resonance spectroscopy (EPR) characterization demonstrate the existence of oxygen vacancies in the catalyst. This system can achieve deep deoxygenation while reducing hydrogen consumption and carbon loss.